Minimal Mass Blowup Solutions for the Patlak‐Keller‐Segel Equation. Issue 10 (16th August 2018) - Ghoul, Tej‐Eddine; Masmoudi, Nader
Abstract: We consider the parabolic‐elliptic Patlak‐Keller‐Segel (PKS) model of chemotactic aggregation in two space dimensions which describes the aggregation of bacteria under chemotaxis. When the mass is equal to 8π and the second moment is finite (the doubly critical case), we give a precise description of the dynamic as time goes to infinity and extract the limiting profile and speed. The proof shows that this dynamic is stable under perturbations. © 2018 Wiley Periodicals, Inc.